オキサリプラチン誘起末梢神経障害（OIPN）への血小板由来HMGB1の関与：抗血小板薬のOIPN予防効果について - 川畑, 篤史; 王, 登莉; 岸本, 彩野; 堂本, 莉紗; 松永, 浩明; 坪田, 真帆; 松本, 亜紗菜; 西堀, 正洋; 関口, 富美子 (日本薬理学会年会要旨集, 2022)
HMGB1, a nuclear protein, once released extracellularly, promotes inflammation and pain. We have shown the involvement of macrophage-derived HMGB1 in chemotherapy-induced peripheral neuropathy (CIPN) caused by paclitaxel, bortezomib or vincristine, and of non-macrophage cell-derived HMGB1 in CIPN caused by oxaliplatin (OIPN). Given the involvement of platelet-derived HMGB1 in thrombosis, we asked whether the pathogenesis of OIPN would involve platelet-derived HMGB1 in rodents. In rat platelet-rich plasma (PRP), thrombin induced HMGB1 release from platelets. An anti-CD42b platelet-depleting antibody dramatically decreased platelet count and increased plasma HMGB1 levels in mice, leading to OIPN development after subsequent oxaliplatin treatment at a subeffective dose. Splenectomy almost doubled platelet count and accelerated OIPN development. Repeated oral administration of different antiplatelet agents, aspirin, clopidogrel, cilostazol and ozagrel, prevented OIPN development in mice and/or rats. In rats subjected to repeated treatment with oxaliplatin, HMGB1 levels dramatically decreased in PRP, but tended to increase in platelet-poor plasma. Together, our study provides novel evidence for a critical role of platelet-derived HMGB1 in OIPN development, and suggests the usefulness of antiplatelet agents to prevent severe OIPN.